To the features of lymphatic channel of digestive tube of small cattle - Колич, Н. Б.; Скрипка, М. В. (Scientific Progress & Innovations, 2015)
From the mucous membrane of the different parts of oral cavity the outflow of lymph is carried out by superficial and deep lymphatic vessels to regional lymph nodes. The mucous and muscular membranes of proventriculus have well developed lymphatic channel, consisting of meandering capillaries with blind outgrowths. The lymphatic capillaries with flask-shaped protrusions are located in serosa. The capillaries, interconnecting with each other, form a capillary network. In 70 % of cases the outflow of lymph from the omasum regional lymph nodes is completed in pancreatic lymph node.